Mengenal Desa Sesepan Melalui QR Code: Sejarah Dalam Genggaman: Pengabdian - Eni Rakhmawati; Uyuun Muzizah Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Village history is often neglected and not taught formally to the younger generation. Lack of knowledge of village history can have an impact on the lack of pride in the place of residence which has the potential to reduce active participation in preserving traditional values. To reduce this impact, the IBN Tegal Posko 21 KKN Student Team held a QR Code digitalization work program to learn about the history of Sesepan Village with the aim of providing local history education as a step to strengthen village identity. The method used in this study is a qualitative research method with more emphasis on analyzing a condition through thinking, data collection techniques through observation and documentation. From the results of the study, it can be concluded that the use of QR Code technology can increase public awareness of village history which can later be accessed through platforms digital.